2010
DOI: 10.1007/s10719-010-9305-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the carbohydrate binding activity of the tobacco lectin

Abstract: At present the three-dimensional structure of the tobacco lectin, further referred to as Nictaba, and its carbohydrate-binding site are unresolved. In this paper, we propose a three-dimensional model for the Nictaba domain based on the homology between Nictaba and the carbohydrate-binding module 22 of Clostridium thermocellum Xyn10B. The suggested model nicely fits with results from circular dichroism experiments, indicating that Nictaba consists mainly of β-sheet. In addition, the previously identified nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Structurally related proteins often share similar molecular functions (Brylinski and Skolnick, 2008;Drew et al, 2011;Rentzsch and Orengo, 2013). This is supported by two tryptophan resisdues, which were shown to be indispensable for lectin activity of Nictaba, are conserved in most of the GmNictaba domain sequences (Schouppe et al, 2010). These Nictaba homologues most likely represent functional carbohydrate-binding proteins.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Structurally related proteins often share similar molecular functions (Brylinski and Skolnick, 2008;Drew et al, 2011;Rentzsch and Orengo, 2013). This is supported by two tryptophan resisdues, which were shown to be indispensable for lectin activity of Nictaba, are conserved in most of the GmNictaba domain sequences (Schouppe et al, 2010). These Nictaba homologues most likely represent functional carbohydrate-binding proteins.…”
Section: Discussionmentioning
confidence: 93%
“…Analysis revealed that, like Nictaba (Schouppe et al, 2010), the soybean homologue also consists of b-sheets. Structurally related proteins often share similar molecular functions (Brylinski and Skolnick, 2008;Drew et al, 2011;Rentzsch and Orengo, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the future, the interaction of Nictaba with histone proteins will have to be confirmed by other biochemical, genetic, and microscop- ical techniques. Negative control experiments with a Nictaba mutant protein affected in its carbohydratebinding activity (Schouppe et al, 2010) could also be useful to prove the interaction with histone proteins.…”
Section: Resultsmentioning
confidence: 99%